La iniciación deportiva y recreativa para la intervención comunitaria en los adolescentes de 11 a 15 años del barrio La Cocha cantón Latacunga, provincia de Cotopaxi 2013-2014 - Chicaiza Toapanta, Doris Elizabeth (2015)
This research had the purpose to analyze the beginning of recreational sports into the community to the teenagers between 11 to 15 years old, located in la Cocha neighborhood in Latacunga, Cotopaxi Province. The teenagers between 11 to 15 years old do not practice the recreational sports activities in their free time. It was considered a scientific problem the following question: What methodological strategy will be better to promote the beginning of recreational sports as a mechanism into the community? It was applied the inductive-deductive, analytical-synthetic method and also as a date collection technique it was used the interview to the directors and the surveys to the teenagers from la Cocha neighborhood. The beginning of recreational sports activities is easily to relate the leisure time with sports activities into to the teenagers requirements. The Project proposal about the beginning of recreational sports into the teenagers is an authentic strategy to improve their quality of life in order to avoid the sedentary lifestyle at an early age.